388 Haemodynamic arterial changes in heart failure: a proposed new paradigm of heart and vessels failure. The Copernican revolution?. (8th December 2021) - Galati, Giuseppe; Germanova, Olga; Iozzo, Renato V.; Buraschi, Simone; Germanov, Andrey; Germanov, Vladimir; Fedorina, Marina; Senni, Michele; Margonato, Alberto
Abstract: Aims: Although heart failure (HF) is one of the most common conditions affecting the heart, little attention has been placed on the role of arteries in contributing to the progression of this disease. We sought to determine the haemodynamic change of arteries in HF patients subdivided according to left ventricular ejection fraction. The major goal was to establish the active compensatory role of arteries in HF. Methods and results: Using sphygmography, we systematically studied a cohort of 228 HF patients and 52 healthy controls. We focused on the common carotid as the main elastic artery and the posterior tibial as the main muscular artery (Figure 1). Moreover, we categorized the three HF groups, HFrEF, HFmrEF, HFpEF, into two subgroups (A and B) according to the presence or absence of HF signs at baseline. We discovered that all the parameters of measured arterial kinetics, i.e. work, power, acceleration, and speed, were significantly increased ( P < 0.001 by one-way ANOVA) in the groups without HF signs. In contrast, all the arterial kinetics parameters were significantly reduced ( P < 0.001) in the groups exhibiting HF signs. Similar results were obtained in both types of arteries and were consistently observed across all the three different types of HF, although with some differences in magnitude. Finally, we discovered that HFpEF patients exhibited more compromised arterial function vis-à-vis HFrEF patients [Figure 2: Patients disposition (Top) and quantification of arterial kinetics and haemodynamic parameters (Down) from the common carotid artery ( A ) and the posterior tibial artery ( B )]. Conclusions: We provide the first documentation of an active compensatory role of arteries during HF. Mechanistically, we explain these findings by a dual activity of large arteries accomplished via an active propulsive work and a concurrent haemodynamic suction. These underestimated arterial functions partially compensate for the heart dysfunction in HF, underlining a key interplay between the heart and the vessels. We propose a new paradigm that we define as 'heart and vessels failure' that explicitly focuses on both heart and vessels' interaction during the progression of HF.